Determining the effect of reinforcing asphalt-concrete coating with synthetic nets on its performance indicators - Onyshchenko, Artur; Kovalchuk, Vitalii; Husev, Dmytro; Anishchenko, Dmitry; Tymoshyn, Maksym; Tsekhansky, Oleg; Rubliov, Andrii; Mel'nyk, Ihor (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is an asphalt concrete cover, the upper layer of which is reinforced with the synthetic material GlasGrid. The subject of research is the performance indicators of asphalt concrete coating. Experimental studies on the effect of reinforced asphalt concrete with synthetic nets on the evolution of rutting and bond strength between layers have been conducted. It has been established that reinforcing the asphalt concrete coating with synthetic nets reduces rutting. At 10,000 load cycles and a temperature of 50 °C, the average value of the rut depth in slab samples without a reinforcing joint was 3.8 mm, and at a temperature of 60 °C – 3.7 mm. In the case of reinforcing the upper layer with a GlasGrid®GG100 net, the depth of the rut at an operating temperature of 50 °C was 3.3, and at an operating temperature of 60 °C – 2.6 mm. With a total number of 20,000 load cycles, the average value of the rut depth without reinforcement of the slab sample is 7.5 mm, and with reinforcement – 5.9 mm. It was established that the rutting resistance of slab samples with reinforcing synthetic nets, in comparison with slab samples without reinforcing material, after the first stage of testing was 13.2 % and 29.7 % after the second stage of testing. It has been established that the maximum vertical shear force that occurs during the destruction of asphalt concrete layers without reinforcement is higher than asphalt concrete layers reinforced with a synthetic mesh. The values of the vertical shear forces without reinforcing the samples are 21.63 kN and 18.46 kN when the samples are reinforced with a synthetic mesh. At the same time, the maximum shear stresses between layers of asphalt concrete core samples without reinforcement are 1.169 MPa, and with reinforcement – 0.988 MPa. Reinforcing the upper layer of the asphalt concrete coating with synthetic meshes will lead to an increase in the durability of the asphalt concrete coating along road sections